THE ACCESS TO JUSTICE IN SYNERGIZING PAYMENT OBLIGATIONS OF SPECIAL MINING BUSINESS LICENSE HOLDERS WITH TAX COMPLIANCE IN INDONESIA - Pramana, Yudha; Hermawan, Anis Wahyu; Barus, Leo B (UNISSULA, 2022)
The obligations of the Special Mining Business License (IUPK) holders to the Government are only given without the active participation of the DGT and the central and local governments to test IUPK compliance as taxpayers. These obligations have the potential to ignore Article 33 and Article 23A of the 1945 Constitution. Based on the normative juridical study using the access to justice and the sustainable development approach, two conclusions are drawn. First, the enactment of several regulations shows that the IUPK's obligation to pay 4% to the Central Government and 6% to the Regional Government from net profits is only given, based on financial reports that have been audited by a public accountant. Second, Article 129 of the Minerba Law, Article 4 (1), Article 6 (1), and Article 9 (1) of the Income Tax Law, as well as Article 15 (3) of PP No. 37 of 2018 must be implemented through monitoring, evaluation, and regular audits of net profits before taxable income on the actual self-assessment reporting conducted by IUPK. It is proposed to make joint audit rules in testing compliance with good mining practice and IUPK obligations, as well as compliance of filling and actual payment of taxes owed.